Forest Fire Dynamics Over a Decade in Mappi District, South Papua: Hotspot Trends and Burned Areas Estimation Using MODIS Data - Nurhayati, Ati D; Satriawan, Handi; Putri, Citra Septriantri (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Forest and land fires have become an annual occurrence in South Papua Province over the past decade, with Mappi District identified as a fire-prone hotspot. This study analyzes hotspot trends and dynamics from 2012 to 2021 and estimates burned areas using Terra/Aqua Moderate Resolution Imaging Spectroradiometer (MODIS)satellite data and ArcMap 10.8. The highest number of hotspots was recorded in 2015 (3,879), with 36.5% occurring on peatland and 63.5% on mineral soils. A historical hotspot analysis pinpoints the prevalence of fire incidents between July and October, highlighting the necessity for intensified prevention measures before July. Furthermore, a significant linear regression is established between annual hotspot numbers and rainfall in Mappi District (p-value = 0.006), signifying the impact of climatic factors on fire occurrences. The largest burned area, estimated at 134,051.74 hectares, also occurred in 2015, coinciding with a strong El Niño event. More importantly, these fires occurred not only on mineral soil but also on peatland areas. Hence, this study highlights the critical need to prioritize comprehensive forest and land fire management in Mappi District, South Papua Province.